Comparison of 27-gauge and 25-gauge vitrectomy in the management of tractional retinal detachment secondary to proliferative diabetic retinopathy. - Po-Lin Chen (Public Library of Science (PLoS), 2021)
Objective To compare surgical outcomes between 27 and 25-gauge vitrectomy in proliferative diabetic retinopathy (PDR) with tractional retinal detachment (TRD). Methods This retrospective study was conducted to compare the intraoperative status, operation time, use of instruments, endotamponade substance, wound suture number, and iatrogenic break, between 27 and 25-gauge vitrectomy in 43 eyes afflicted by PDR with TRD. The post-surgical results, best-corrected visual acuity, intraocular pressure, recurrent vitreous haemorrhage, and re-operation rate were regularly followed up for 6 months. Results Patients in the 25 and the 27-gauge groups did not differ significantly in terms of pre-surgical conditions, such as age, gender, pre-existing glaucoma, best-corrected visual acuity (BCVA) and the severity of their TRD. The mean operation time was 56.7 minutes in the 27-gauge group and 63.7 minutes in the 25-gauge group (p = 0.94). There is significantly less use of micro forceps in the 27-gauge group (p = 0.004). No difference between micro scissors and chandelier usage were noted; neither was their difference in iatrogenic retinal breaks. Significantly fewer wound sutures were noted in the 27-gauge group (p < 0.001). The post-operative results revealed no significant difference in ocular hypertension, hypotony, BCVA improvement, recurrent vitreous haemorrhage and re-operation rate. Conclusions The 27-gauge vitrectomy system offers comparable surgical outcomes in PDR with TRD. The 27-gauge vitrectomy system is suitable for complicated retinal surgery.